2017
DOI: 10.1186/s13613-017-0241-1
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology of sepsis in Catalonia: analysis of incidence and outcomes in a European setting

Abstract: BackgroundUp-to-date identification of local trends in sepsis incidence and outcomes is of considerable public health importance. The aim of our study was to estimate annual incidence rates and in-hospital mortality trends for hospitalized patients with sepsis in a European setting, while avoiding selection bias in relation to different complexity hospitals.MethodsA large retrospective analysis of a 5-year period (2008–2012) was conducted of hospital discharge records obtained from the Catalan Health System (C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
42
4
5

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 70 publications
(60 citation statements)
references
References 33 publications
6
42
4
5
Order By: Relevance
“…A large observational study in a European setting revealed an estimated mean sepsis incidence of 212.7 cases per 100,000 inhabitants with an annual incidence increase of 7.3%. In Brazil, sepsis incidence was 36.3 per 1000 patient-days and sepsis mortality was 55.7% [12].…”
Section: Sepsis As a Healthcare Problemmentioning
confidence: 99%
“…A large observational study in a European setting revealed an estimated mean sepsis incidence of 212.7 cases per 100,000 inhabitants with an annual incidence increase of 7.3%. In Brazil, sepsis incidence was 36.3 per 1000 patient-days and sepsis mortality was 55.7% [12].…”
Section: Sepsis As a Healthcare Problemmentioning
confidence: 99%
“…A substantial number of patients with sepsis require intensive care unit (ICU) admission for close monitoring and supportive therapy 1. Close monitoring of conditions such as unstable vitals and circulatory haemodynamics, oxygen supply and demand, and respiratory dysfunction are key components in the successful treatment of severe sepsis and septic shock.…”
Section: Introductionmentioning
confidence: 99%
“…Fast spreading bacterial infections induce acute infections, critical illnesses as meningitis, as well as life-threatening conditions as sepsis. 1,2 In particular, sepsis with a mortality rate of 30% [3][4][5][6][7] requires fast and accurate diagnosis as the survival chances decreases by 7-8% for every hour that the infection remains untreated. [8][9][10] Rapid, sensitive and quantifiable bacterial detection from patient blood is thus a clinical demand.…”
Section: Introductionmentioning
confidence: 99%